Structural Model of Religiosity of the Engineering Profession of the Indonesian Engineers Association - Yunus, Ruslan Moh.; Wibisono, Muhammad Yusuf; Truna, Dody S. (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
This research asks questions about what engineers do and how they express their professional demands as well as their religious demands. This research is prioritized to determine the dynamics of engineering diversity through the relationship between the religiosity of Muslim engineers and future engineering-technology risks in Indonesia. To achieve its objectives, this research uses a holistic-integrative approach as a way to explore the relationship between engineers' religiosity and engineering-technology risks in Indonesia. This research begins with quantitative data collection and Maximum Likelihood Estimate (MLE) analysis, followed by modeling using the Structural Equation Model application (Structured Equation Modelling-Partial Least Square or SEM-PLS) version 3.0. The research begins with observing literature to obtain the main dimensions of religiosity, then selecting and determining the main and important dimensions of the Islamic religion. constructing each dimension into sub-dimensions and attributes that consist of diversity. using a modified worldview approach. The religiosity structure developed consists of 6 main dimensions, namely: dimensions of universal awareness (X1), universal views (X2), core values (X3); identity dimension (X4), observed behavior dimension (X5) and institutional culture dimension (X6). To test the structural model of religiosity, this research has collected field data obtained from 45 graduates of the engineering professional program as research respondents spread across Central Sulawesi and South Sulawesi.